Strategy Program for Reducing Doubt on Covid-19 Vaccination in Tambraw Regency, West Papua - Butet Agustarika; Alva Cherry Mustamu; Situmorang Panel (Universitas Malahayati Lampung, 2022)
ABSTRACT Covid-19 vaccination aims to minimize the spread of Covid-19, reduce the number of positive and death due to Covid-19, reach the immunity group (herd immunity ) and protect the Public from Covid-19 to stay productive by social and economic. Some strategies can increase reception of booster vaccines, i.e. advocacy by local, national and international for equal access to COVID-19 vaccines, tests and treatments, calling for and monitoring action specific required from producers, governments and multilateral actors. Mobilize and empower the community, including through social media and networks community, to produce the influential vaccine. Sue and overcome Contributing misinformation and misperception to doubt vaccine. Purpose implementation of activity programs Public this is doing implementation strategy World Health Organization recommended vaccinations, namely seminars and giving non-financial incentives as well as board advertisement capable for lower level doubt booster vaccine. Devotion Public this is conducted with several steps that is conduct seminars on the importance of vaccinating basic and advanced (booster) covid-19, do publication about covid-19 vaccine using leaflets, leaflets and boards billboard on the corner Street, as well as implementation vaccination with gift incentive in form goods, needs a tree. Next held vaccination start and booster at the same time given goods need the tree. This Seminar and FGD held inviting representatives from agency government related, police and soldier, Puskesmas and heads of the district. Problems found is awareness of Public consequence, ignorance of the importance of vaccination, and distance and access to vaccination implementation. Together To do follow-up and share the task. Vaccination this in progress for one day and ends with distribution needs tree for participant vaccination. Attendees in activity vaccination this as many as 572 people, did vaccination dose first as much as 134, dose second as many as 359 people and continued as many as 79 people. The results of service Public this capable for lower doubt Public to implementation vaccination beginning nor continued. The problem in society consequence implementation of vaccination is a lack of information and access to vaccination. Moment conducted solving problem and shared task on each agency government, then found a solution that is deployment information and accommodate Public going to the place vaccination. Because of that, interest in the Public Becomes increased for vaccination. Community service programs in the future can be focused on increasing public awareness which also involves relevant government agencies. Keywords: Booster, Vaccine, Public Devotion, Herd Immunity